Ecdysteroid Hormones Link the Juvenile Environment to Alternative Adult Life Histories in a Seasonal Insect - Oostra, Vicencio (2014)
The conditional expression of alternative life strategies is a widespread feature of animal life and a pivotal adaptation to life in seasonal environments. To optimally match suites of traits to seasonally changing ecological opportunities, animals living in seasonal environments need mechanisms linking information on environmental quality to resource allocation decisions. The butterfly Bicyclus anynana expresses alternative adult life histories in the alternating wet and dry seasons of its habitat as endpoints of divergent developmental pathways triggered by seasonal variation in preadult temperature. Pupal ecdysteroid hormone titers are correlated with the seasonal environment, but whether they play a functional role in coordinating the coupling of adult traits in the alternative life histories is unknown. Here, we show that manipulating pupal ecdysteroid levels is sufficient to mimic in direction and magnitude the shifts in adult reproductive resource allocation normally induced by seasonal temperature. Crucially, this allocation shift is accompanied by changes in ecologically relevant traits, including timing of reproduction, life span, and starvation resistance. Together, our results support a functional role for ecdysteroids during development in mediating strategic reproductive investment decisions in response to predictive indicators of environmental quality. This study provides a physiological mechanism for adaptive developmental plasticity, allowing organisms to cope with variable environments.